2008
DOI: 10.1194/jlr.m800244-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Differences in DBA/1J and DBA/2J reveal lipid QTL genes

Abstract: Recent advances in mouse genomics have revealed considerable variation in the form of single-nucleotide polymorphisms (SNPs) among common inbred strains. This has made it possible to characterize closely related strains and to identify genes that differ; such genes may be causal for quantitative phenotypes. The mouse strains DBA/1J and DBA/2J differ by just 5.6% at the SNP level. These strains exhibit differences in a number of metabolic and lipid phenotypes, such as plasma levels of triglycerides (TGs) and HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…Future studies could center on tracking and identification of QTL that modify particular cardiac disease-related physiological processes. Previous studies have demonstrated the feasibility of using the genetic homogeneity of inbred mouse strains to isolate and identify physiologically significant QTL (2,6,13,20,21,48,49). In this study, we observed significant functional differences between inbred strains that were evident when subjected to the stresses of ischemia/reperfusion, ␤-blockade, and acute hypoxia.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Future studies could center on tracking and identification of QTL that modify particular cardiac disease-related physiological processes. Previous studies have demonstrated the feasibility of using the genetic homogeneity of inbred mouse strains to isolate and identify physiologically significant QTL (2,6,13,20,21,48,49). In this study, we observed significant functional differences between inbred strains that were evident when subjected to the stresses of ischemia/reperfusion, ␤-blockade, and acute hypoxia.…”
Section: Discussionsupporting
confidence: 57%
“…Even in the absence of engineered or known naturally occurring mutations, different inbred mouse strains can vary drastically in their susceptibility to clinically relevant diseases. Previous reports have taken advantage of this naturally occurring variation in susceptibility to a particular disease to identify quantitative trait loci (QTL) that modify disease pathogenesis (2,6,13,48,49).…”
mentioning
confidence: 99%
“…While the contrast in parental blood pressure phenotype would be less than in contrasts between SHR and normotensive strains 57 genetic background effects may be much smaller 8 and the shared IBD would reduce the total region of the genome in which differences in blood pressure could arise. The same approach has recently been used in closely related mouse lines to yield high resolution mapping of trait genes 9 .…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies on the QTL affecting lipid and glucose levels in both humans and rodents (1,29,49). However, studies on QTL for clinical-chemical traits other than lipid levels are still scarce when it comes to pigs.…”
mentioning
confidence: 99%